JAVANESE ISLAM AND GLOBALIZATION: A STUDY ON THE SUSTAINABILITY THE ABOGE ISLAM COMMUNITY IN INDONESIA - M Ali Sofyan; Tri Wahyuni; Win Listyaningrum Arifin (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2023)
The indigenous religion of Java has a longer historical existence compared to the currently recognized state religions. Similarly, Javanese Islam has evolved through religious syncretism with Javanese culture. Javanese Islam has served as a means to reconcile the two opposing poles of this entity, as well as a way to attract followers. Aboge Islam in Purbalingga, Central Java is one form of Javanese Islam. The existence of Aboge Islam is facing increasing threats, particularly in the era of globalization. This article will provide an overview of the current reality, obstacles, and threats faced by the Aboge Islamic community, and discuss their future. This research is conducted using the qualitative ethnographic method. Data was collected through in-depth interviews with members of the Aboge Muslim community, as well as observations and document studies. The findings revealed that the Aboge Muslim community has undertaken various adaptation processes as a survival strategy to maintain its existence amidst the challenges posed by globalization. This form of adaptation is the inheritance of community values by passing down their traditional values to the younger generation, which includes 'ngormati leluhur' (the practices of ancestor worship),